Isolation and characterization of a novel cold-adapted esterase, MtEst45, from Microbulbifer thermotolerans DAU221 - Yong-Suk eLee (Frontiers in Microbiology, 2016)
A novel esterase, MtEst45, was isolated from a fosmid genomic library of Microbulbifer thermotolerans DAU221. The encoding gene is predicted to have a mass of 45,564 Da and encodes 495 amino acids, excluding a 21 amino acid signal peptide. MtEst45 showed a low amino acid identity (approximately 23–24%) compared with other lipolytic enzymes belonging to Family III, a closely related bacterial lipolytic enzyme family. MtEst45 also showed a conserved GXSXG motif, G131IS133YG135, which was reported as active site of known lipolytic enzymes, and the putative catalytic triad composed of D237 and H265. Because these mutants of MtEst45, which was S133A, D237N, and H265L, had no activity, these catalytic triad essential for the enzyme catalysis. MtEst45 was overexpressed in Escherichia coli BL21 (DE3) and purified via His-tag affinity chromatography. The optimal pH and temperature of MtEst45 were estimated to be 8.17 and 46.27°C by response surface methodology, respectively. Additionally, MtEst45 was also active between 1–15°C. The optimal hydrolysis substrate for MtEst45 among p-nitrophenyl esters (C2–C18) was p-nitrophenyl butyrate, and the Km and Vmax values were 0.0998 mM and 550 μmol/min/mg of protein, respectively. MtEst45 was strongly inhibited by Hg2+, Zn2+, and Cu2+ ions; by phenylmethanesulfonyl fluoride; and by β-mercaptoethanol. Ca2+ did not affect the enzyme’s activity. These biochemical properties, sequence identity, and phylogenetic analysis suggest that MtEst45 represents a novel and valuable bacterial lipolytic enzyme family and is useful for biotechnological applications.